Corporate Social Responsibility Communication by Chemical Companies on Social Networks in the Czech Republic - Tetřevová, Liběna; Hozák, Miroslav (Wydawnictvo SIGMA-NOT, 2019)
Intensity and structure of communication of socially responsible activities by chem. companies operating in the Czech Republic on the social Facebook and Linkedln networks were evaluated. Attention of the companies was primarily focused on the communication of philanthropic responsibility activities (Facebook) and economic ones (Linkedln). Ethical responsibility activities were communicated to the least extent.
Společensky odpovědné komunikování chemických firem v České republice na sociálních sítích
Keywords: corporate social responsibility; CSR communication; social networks; chemical industry; Facebook; LinkedIn; společenská odpovědnost firem; CSR komunikování; sociální sítě; chemický průmysl; Facebook; LinkedIn